Thalamic Ryanodine Receptors Are Involved in Controlling the Tonic Firing of Thalamocortical Neurons and Inflammatory Pain Signal Processing - Cheong, Eunji; Kim, Chanki; Choi, B. Jiwon; Sun, Minjeong; Shin, Hee-Sup (SOC NEUROSCIENCE, 2011)
Ryanodine receptors (RyRs) are highly conductive intracellular Ca(2+) release channels which are widely expressed in the CNS. They rapidly increase the intracellular Ca(2+) concentrations in neuronal cells in response to Ca(2+) influx through voltage-gated Ca(2+) channels. A previous study reported that RyRs were expressed in thalamocortical (TC) neurons, but their physiological function has remained elusive. Here, we show that the activation of RyRs in TC neurons in mice decreases their tonic firing rate while blocking them induces the opposite response. Furthermore, activation of RyRs in ventroposteriomedial/ventroposteriolateral nuclei reduces the behavioral responses to inflammatory pain and blocking them increases the responses. This study highlights the importance of the intracellular Ca(2+) release via RyRs in controlling the excitability of TC neurons and in inflammatory pain signal processing in the thalamus.
Keywords: CA2+ CHANNELS; NOCICEPTION; MICE